CHARACTER EDUCATION IN ISLAMIC EDUCATION INSTITUTIONS: A Study on the Impact of Lecturer Competence at IAIN Lhokseumawe - Rahmah, Syarifah; Fadhli, Muhammad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This study aims to determine the effect of lecturer competence on the character of students at IAIN Lhokseumawe. The research method used is quantitative with a path analysis model. The research subjects were students of IAIN Lhokseumawe. With a total sample of 351 people. Sampling was done using the proportional random sampling technique. Based on the research findings, professional competence has the strongest and most significant impact on character development followed by pedagogical, social, and personality competencies. This finding implies that higher education institutions need to develop lecturers' competencies, especially professional competencies to realize better character education among universities.Keywords: pedagogical, professional, personality, social, Islamic student character